2017
DOI: 10.1111/cgf.13205
|View full text |Cite
|
Sign up to set email alerts
|

Steering the Craft: UI Elements and Visualizations for Supporting Progressive Visual Analytics

Abstract: Progressive visual analytics (PVA) has emerged in recent years to manage the latency of data analysis systems. When analysis is performed progressively, rough estimates of the results are generated quickly and are then improved over time. Analysts can therefore monitor the progression of the results, steer the analysis algorithms, and make early decisions if the estimates provide a convincing picture. In this article, we describe interface design guidelines for helping users understand progressively updating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…They found progressive visualizations outperformed blocking visualizations, even giving comparable performance to ideal instantaneous visualizations. Similar results can be elicited from Badam et al's user study [32], where a progressive interface, InsightsFeed, and its instantaneous version showed similar performance in terms of answer accuracy and user preferences.…”
Section: Progressive Systemssupporting
confidence: 84%
“…They found progressive visualizations outperformed blocking visualizations, even giving comparable performance to ideal instantaneous visualizations. Similar results can be elicited from Badam et al's user study [32], where a progressive interface, InsightsFeed, and its instantaneous version showed similar performance in terms of answer accuracy and user preferences.…”
Section: Progressive Systemssupporting
confidence: 84%
“…Similarly, Rosenbaum et al [17] allow the user to steer the visualization and prioritize data regions of interest. InsightsFeed [18] demonstrates interface controls and visualization augments for progressive visualization steering.…”
Section: Progressive Visual Analyticsmentioning
confidence: 99%
“…But this is rarely done. One reason observed in recent user studies may be that users seem uneasy to judge the trustworthiness of partial data shown in unfinished visualizations at the same time [19].…”
Section: Figurementioning
confidence: 99%
“…This happens when employing an inadequate sampling technique, but can in particular be observed when performing no sampling at all and simply partitioning the data as is. One solution is to randomize the data in a preprocess before loading it into the PVA system [19], (Section 4). This simple, yet effective solution is suited for scenarios in which one does not have access to the source of a PVA system and cannot add improved sampling functionality to it.…”
Section: Support Handling Fluctuating Progressionsmentioning
confidence: 99%
See 1 more Smart Citation